Co-authorship Pattern in Research on Energy Sector: Social Network Analysis - Aisyah, Siti; Hardiyati, Ria (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2019)
A nation capacity to provide clean and affordable energy is crucial for the development of its economy. Indonesia energy mix still rely heavily on fossil fuels, but a concerted effort to explore a more sustainable energy has been laid out by the government, including promoting studies and providing incentives for research in the area of sustainable energy. This paper tries to examine the trend of energy research in Indonesia, the theme of research in the field of energy and to find out which institution has conducted a rigorous research and actively producing publications in this field. The study uses data of international research publications from World of Science (WOS) during 1997-2014. Data Analysis using Social Network Analysis (SNA) with UCINET, NetDraw, and VOSViewer software. The result shows that the number of international publications on energy in Indonesia are increasing and most publications are of research collaboration with institutions from other country. Based on keywords that frequently appear which are biomass, biodiesel, and ethanol, it can be concluded that popular research theme on energy in Indonesia is renewable energy. This paper concludes with the findings on institutions with the highest rank in renewable energy publications, those are Institut Teknologi Bandung (ITB), Universitas Gadjah Mada (UGM), Institut Pertanian Bandung (IPB), and Lembaga Ilmu Pengetahuan Indonesia/Indonesian Institute of Sciences (LIPI). Research collaborations with institutions from around the globe will improve the performance of research and development bodies in Indonesia, which will only benefit the economy in the long run.